2011
DOI: 10.1177/0148607111414580
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid and Arachidonic Acid Prevent Essential Fatty Acid Deficiency and Hepatic Steatosis

Abstract: Objectives Essential fatty acids are important for growth, development, and physiologic function. Alpha-linolenic acid and linoleic acid are the precursors of docosahexaenoic and arachidonic acid, respectively, and have traditionally been considered the essential fatty acids. However, we hypothesized that docosahexaenoic acid and arachidonic acid can function as the essential fatty acids. Methods Using a murine model of essential fatty acid deficiency and consequent hepatic steatosis, we provided mice with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…The activation of PPAR-γ was shown to have a relationship with expression of collagen type I induced by TGF-β1 (Bian et al, 2013) and inhibit hepatic stellate cell activation and progression of fibrosis (Attia et al, 2013). Studies have indicated that arachidonic acid is involved in oxidative stress and in inflammatory response (Holownia et al, 2014;Le et al, 2012;Xie et al, 2015) which was also been proved in our GO analysis. ALDH2 and ALDH7A1 were involved in glycolysis/Gluconeogenesis and glycerolipid metabolism, and the results of qRT-PCR and Western blot showed that the expression of ALDH2 and ALDH7A1 decreased after liver injury.…”
Section: Discussionsupporting
confidence: 70%
“…The activation of PPAR-γ was shown to have a relationship with expression of collagen type I induced by TGF-β1 (Bian et al, 2013) and inhibit hepatic stellate cell activation and progression of fibrosis (Attia et al, 2013). Studies have indicated that arachidonic acid is involved in oxidative stress and in inflammatory response (Holownia et al, 2014;Le et al, 2012;Xie et al, 2015) which was also been proved in our GO analysis. ALDH2 and ALDH7A1 were involved in glycolysis/Gluconeogenesis and glycerolipid metabolism, and the results of qRT-PCR and Western blot showed that the expression of ALDH2 and ALDH7A1 decreased after liver injury.…”
Section: Discussionsupporting
confidence: 70%
“…An omega-3 FA rich diet (DHA) was designed to mimic the FA composition of cold water fish (21, 22), with an omega-3 to omega-6 FA ratio of 20:1 provided as DHA and arachidonic acid (AA; 20:4n-6; omega-6 FA). In contrast an omega-6 FA rich diet (SOY) was designed to mimic the standard western diet, with fat provided as soybean oil and thus containing an omega-6 to omega-3 FA ratio of ~8:1 provided as linoleic acid (LA; 18:2n-6; omega-6 FA) and alpha-linolenic acid (ALA; 18:3n-3; omega-3 FA).…”
Section: Resultsmentioning
confidence: 99%
“…To this end, an omega-3 fatty acid-rich diet was designed to mimic the fatty acid composition of cold water fish (Le et al , 2012), with an omega-3 to omega-6 fatty acid ratio of 20:1 provided as docosahexaenoic acid (DHA; 22:6n-3; omega-3 fatty acid) and arachidonic acid (AA; 20:4n-6; omega-6 fatty acid). In contrast, an omega-6 fatty acid-rich diet was designed to mimic the standard Western diet, with fat provided as soybean oil and thus containing an omega-6 to omega-3 fatty acid ratio of approximately 8:1 provided as linoleic acid (LA; 18:2n-6; omega-6 fatty acid) and alpha-linolenic acid (ALA; 18:3n-3; omega-3 fatty acid).…”
Section: Resultsmentioning
confidence: 99%